Mental model processes in working memory : implications for usability design. - Patsula, Peter Joseph. (2008)
Grounded in cognitive load theory, levels of processing theory, the facets of WM framework, and dual-process research, this thesis proposes two theoretical propositions related to mental model production in WM and encoding to LTM. The first proposition, "structure processing," posits a domain-general goal-oriented chunking mechanism that facilitates the coordination of associations made into coherent structures in WM to improve performance and retention. The second proposition of "singularity," posits that information processing in WM is directed towards creating a single coherent and parsimonious episodic model that exerts a low cognitive load. To test these propositions, two studies were conducted to investigate navigation performance and retention of a variety of simple and complex Web-based menus treated with structured or unstructured design. The proposition of singularity was assessed in an analysis of pauses during a menu recall task to estimate the number of chunks needed to recall a menu. Participants were also tested for cognitive abilities necessary for coordination, storage, and supervision. Findings provided strong support that structured design improved menu performance and retention, with weak to moderate correlations with coordination. A strong correlation between retention and number of chunks needed to recall a menu was also found.